Imperfect Vaccination Can Enhance the Transmission of Highly Virulent Pathogens. - Andrew F Read; Susan J Baigent; Claire Powers; Lydia B Kgosana; Luke Blackwell; Lorraine P Smith; David A Kennedy; Stephen W Walkden-Brown; Venugopal K Nair (PLoS Biology, 2015)
Could some vaccines drive the evolution of more virulent pathogens? Conventional wisdom is that natural selection will remove highly lethal pathogens if host death greatly reduces transmission. Vaccines that keep hosts alive but still allow transmission could thus allow very virulent strains to circulate in a population. Here we show experimentally that immunization of chickens against Marek's disease virus enhances the fitness of more virulent strains, making it possible for hyperpathogenic strains to transmit. Immunity elicited by direct vaccination or by maternal vaccination prolongs host survival but does not prevent infection, viral replication or transmission, thus extending the infectious periods of strains otherwise too lethal to persist. Our data show that anti-disease vaccines that do not prevent transmission can create conditions that promote the emergence of pathogen strains that cause more severe disease in unvaccinated hosts.